2017
DOI: 10.1016/j.neuroimage.2015.12.050
|View full text |Cite
|
Sign up to set email alerts
|

Decoding negative affect personality trait from patterns of brain activation to threat stimuli

Abstract: IntroductionPattern recognition analysis (PRA) applied to functional magnetic resonance imaging (fMRI) has been used to decode cognitive processes and identify possible biomarkers for mental illness. In the present study, we investigated whether the positive affect (PA) or negative affect (NA) personality traits could be decoded from patterns of brain activation in response to a human threat using a healthy sample.MethodsfMRI data from 34 volunteers (15 women) were acquired during a simple motor task while the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 89 publications
2
26
0
Order By: Relevance
“…NA trait has been also associated with poor prognosis [72] and predictive of onset of major depression [73]. Furthermore, a recent study showed that it is possible to decode individuals NA trait from patterns of brain activation to threat stimuli in a sample of healthy subject [74]. Our results, corroborate with these previous studies and support the evidence that Negative Affect trait might 755 have important clinical implications for depression.…”
supporting
confidence: 89%
“…NA trait has been also associated with poor prognosis [72] and predictive of onset of major depression [73]. Furthermore, a recent study showed that it is possible to decode individuals NA trait from patterns of brain activation to threat stimuli in a sample of healthy subject [74]. Our results, corroborate with these previous studies and support the evidence that Negative Affect trait might 755 have important clinical implications for depression.…”
supporting
confidence: 89%
“…The analysis aimed to test whether participants' diffusion of responsibility could be decoded from resting‐state connectivity patterns of dACC and putamen [Fernandes et al, ]. This complemented the univariate correlational analysis by providing two primary advantages: (i) the multivariate nature of the analysis enabled the detection of subtle and spatially distributed effects and (ii) the analysis allowed for predicting unseen participants, offering information at the individual rather than at the group level.…”
Section: Methodsmentioning
confidence: 99%
“…The pattern regression analysis was implemented in PRoNTo (http://www.mlnl.cs.ucl.ac.uk/pronto/) and included the following steps [Fernandes et al, ; Schrouff et al, ]: (1) The resting‐state connectivity of dACC and putamen as seeding regions was derived from the seed‐to‐voxel connectivity analysis. (2) The whole brain was split into 116 anatomical regions according to the aal atlas.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…MKL allows to account for brain anatomy (determined by a brain atlas, see section 2.7) and different modalities (such as anatomical/functional data or in the current approach: conditions) during the model estimation by considering each brain region and modality as separate kernels. This approach allows determining the contribution of each brain region (region weights) and condition (condition weights) to the final decision function of the model in a hierarchical manner by simultaneously learning and combining the different linear kernels that are based on support vector machines (SVM) (Rakotomamonjy et al, 2008;Fernandes et al, 2017;Schrouff et al, 2018). Compared to conventional MVPA methods based on whole-brain voxel weight maps, this procedure provides a straight-forward approach to draw inferences on the region level without the need for multiple comparison correction (Schrouff et al, 2018).…”
Section: Multivariate Pattern Analysis (Mvpa)mentioning
confidence: 99%